2021
DOI: 10.1099/mgen.0.000515
|View full text |Cite
|
Sign up to set email alerts
|

Kill and cure: genomic phylogeny and bioactivity of Burkholderia gladioli bacteria capable of pathogenic and beneficial lifestyles

Abstract: Burkholderia gladioli is a bacterium with a broad ecology spanning disease in humans, animals and plants, but also encompassing multiple beneficial interactions. It is a plant pathogen, a toxin-producing food-poisoning agent, and causes lung infections in people with cystic fibrosis (CF). Contrasting beneficial traits include antifungal production exploited by insects to protect their eggs, plant protective abilities and antibiotic biosynthesis. We explored the genomic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(58 citation statements)
references
References 57 publications
6
52
0
Order By: Relevance
“…The ANI values were visualized by heatmap.2 function in the gplots package in the R environment ( , accessed on 10 February 2021). We also confirmed the phylogenetic distribution of the 14 B. gladioli in cladistic structure, which were previously well described by Jones et al [ 32 ]. To cover the full diversity of the population, the representative 22 B. gladioli members were selected from different clades of 206 B. gladioli isolates and compared with 14 B. gladioli as in a study of Lin et al [ 39 ].…”
Section: Methodssupporting
confidence: 91%
See 4 more Smart Citations
“…The ANI values were visualized by heatmap.2 function in the gplots package in the R environment ( , accessed on 10 February 2021). We also confirmed the phylogenetic distribution of the 14 B. gladioli in cladistic structure, which were previously well described by Jones et al [ 32 ]. To cover the full diversity of the population, the representative 22 B. gladioli members were selected from different clades of 206 B. gladioli isolates and compared with 14 B. gladioli as in a study of Lin et al [ 39 ].…”
Section: Methodssupporting
confidence: 91%
“…The ANI-based phylogenomic relationships also validated in cladistic structure, which were previously well described by Jones et al [ 32 ]. We obtained 4392 concatenated core genes by comparing 14 B. gladioli genomes in this study with the genomes of 22 previously reported ( Figure 2 B).…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations